COMPARATIVE STUDY OF BGH PUPR AND GREENSHIP ASSESSMENT CRITERIA ON SGLC BUILDING UGM - Dewi, S.T., M.T. , M.Sc., Cynthia Permata; Kusumawanto, Arif (Department of Civil Engineering, Faculty of Engineering, Universitas Islam Malang, 2024)
The use of green building concepts is growing in response to global climate change and the impact of CO2 emissions. Green building assessment systems have emerged in various countries around the world as a basis for assessing the green level of buildings. Indonesia has two green building assessment systems, namely BGH assessment based on PUPR minister's regulation no 21 of 2021 and Greenship. This research aims to find out the similarities and differences between the two systems and how they are applied to green buildings at SGLC UGM as a case study. This research uses a comparative descriptive method through BGH and Greenship documents. The results showed that both assessment systems have some similarities in terms of energy efficiency, water, waste management and support for the use of renewable energy. The differences between the two systems include certification bodies, document requirements, assessment stages and standard references used. The application of the assessment system to the UGM SGLC building through the BGH candy checklist approach resulted in a score of 66% and a score of 52 on the Greenship assessment. demonstrating that achieving middle-level BGH and Greenship performance is attainable through integrated sustainable design, which serves as a benchmark for future projects aiming to balance environmental performance with local conditions, thereby advancing Indonesia green building agenda and supporting national sustainability goals. Keywords: BGH; Greenship; Green Building Assessment.